Association between 18F-fluorodeoxyglucose-PET/CT and histological grade of uterine endometrial carcinoma - Hiroaki Takagi; Toshiyuki Sasagawa; Takeo Shibata; Hiroshi Minato; Tomoko Takahashi (Elsevier, 2018)
Objective: The incidence of endometrial adenocarcinoma of the uterine corpus has increased in Japan. This study aimed to clarify the relationships between this type of cancer and various data provided by 18F-fluorodeoxyglucose (FDG) accumulation in positron emission tomography/computed tomography (PET/CT). Materials and methods: The study cohort thus comprised 27 patients with endometrial adenocarcinoma who had undergone PET/CT examinations from April 2008 to March 2015. All patients provided informed consent at our hospital. Data from 27 patients with endometrial adenocarcinoma (Grades 1-3) were retrospectively analyzed to determine the relationships between the maximum standardized uptake value (SUVmax), histological grading, tumor size, and rate of positivity for glucose transporter 1, hexokinase II, and glucose-6-phosphatase-α (G6Pase-α). Results: SUVmax values differed significantly between patients with Grade 1 (G1) and Grade 2 (G2) or higher cancer (P = 0.031). For G1 cancer, a negative correlation was found between SUVmax and G6Pase-α (R = −0.475, P = 0.046). The regression coefficient for G6Pase-α was −0.125 (95% CI: −0.165 to −0.084) and the P-value 0.008; thus this difference was significant. Conclusion: PET/CT is a useful test for discriminating between G1 and G2 or higher cancer in patients with endometrial adenocarcinoma of the uterine corpus. In addition, the negative correlation identified between SUVmax and G6Pase-α activity in patients with well-differentiated endometrial cancer may be a novel finding. Keywords: Positron-emission tomography, Standardized uptake value, 18F-fluorodeoxyglucose, Endometrial cancer, Glucose-6-phosphatase